2018
DOI: 10.1080/15592294.2018.1450033
|View full text |Cite
|
Sign up to set email alerts
|

Genipin normalizes depression-like behavior induced by prenatal stress through inhibiting DNMT1

Abstract: Synthetic antidepressants in current use for the complex etiopathogeneses of depression have slow response and remission as well as various unpleasant side effects. As a result, it is imperative to develop new antidepressants with more effectiveness and less severe side effects. Recent studies demonstrated that genipin, the aglycon of geniposide, extracted from Gardenia jasminoides Ellis has antidepressive effects. However, knowledge regarding the molecular mechanisms of its antidepressant effects remains limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
(101 reference statements)
1
15
0
Order By: Relevance
“…However, the sex-specific expression patterns of GR protein in PS offspring suggest that additional mechanisms are involved. Specific DNMTs or demethylase were found to be involved in anxiety-like behavior in adult rodents; it was suggested that these enzymes exert their effects by modifying GR expression in the hippocampus (Cheng et al, 2018;Ye et al, 2018). In support of this possibility, we showed that PS exposure increased DNMT3a expression in the hippocampus of adolescent female rats while decreasing that of Tet-2 in males.…”
Section: Discussionsupporting
confidence: 65%
“…However, the sex-specific expression patterns of GR protein in PS offspring suggest that additional mechanisms are involved. Specific DNMTs or demethylase were found to be involved in anxiety-like behavior in adult rodents; it was suggested that these enzymes exert their effects by modifying GR expression in the hippocampus (Cheng et al, 2018;Ye et al, 2018). In support of this possibility, we showed that PS exposure increased DNMT3a expression in the hippocampus of adolescent female rats while decreasing that of Tet-2 in males.…”
Section: Discussionsupporting
confidence: 65%
“…Melas et al discovered that treating depressive rats with escitalopram could down-regulate the expression of Dnmt1 in prefrontal cortex ( 31 ). And in hippocampus, genipin reduced despair-like traits (assessed via TST and FST) by inhibiting the expression of Dnmt1 and normalizing the expression of BDNF ( 53 ). Additionally, Wright et al found that the expression of Dnmt1 was increased in the central nucleus of amygdala in the depression mouse model established by chronic social failure stress (assessed via a social interaction test (SIT)), but only in the female mice ( 54 ).…”
Section: Dna Methyltransferases In Depressionmentioning
confidence: 99%
“…In this context, it is important to note that in human prostate, methylation of SRD5A2 is regulated by DNA methyltransferase 1 (DNMT1) (44) and that, as demonstrated in animal models, forebrain deletion of DNMT1 (45) or its pharmacological inhibition (44, 46) had antidepressant-like properties.…”
Section: Discussionmentioning
confidence: 99%